A Posteriori Error Estimate of Finite Element Method for the Optimal Control with the Stationary Bénard Problem (Journal of Computational Mathematics, 2018)
In this paper, we consider the adaptive finite element approximation for the distributed optimal control associated with the stationary Bénard problem under the pointwise control constraint. The states and co-states are approximated by polynomial functions of lowest-order mixed finite element space or piecewise linear functions and control is approximated by piecewise constant functions. We give the a posteriori error estimates for the control, the states and co-states.